2009
DOI: 10.1097/qai.0b013e318198a88a
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Among HIV-Infected Persons

Abstract: Objective To describe the prevalence and factors associated with nonalcoholic fatty liver disease (NAFLD) among HIV-infected persons not infected with hepatitis C virus (HCV). Design A cross-sectional study among HIV-infected patients in a large HIV clinic. Methods NAFLD was defined as steatosis among patients without viral hepatitis (B or C) co-infection or excessive alcohol use. The prevalence of NAFLD was identified by ultrasound examination evaluated by two radiologists blinded to the clinic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
161
2
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(191 citation statements)
references
References 48 publications
15
161
2
13
Order By: Relevance
“…8 Several studies addressed the topic with a noninvasive approach and the majority did not exclude patients with HCV coinfection. Two well-designed studies, one assessing HS with ultrasonography 10 and the other with computed tomography (CT) scans, 11 found prevalences of 31% and 37%, respectively. Although the main risk factors found in these studies were metabolic, another study compared two groups of patients with HS and different HIV status; the results showed that HIV-infected patients had lower body mass index (BMI) and lower body fat percentage.…”
mentioning
confidence: 99%
“…8 Several studies addressed the topic with a noninvasive approach and the majority did not exclude patients with HCV coinfection. Two well-designed studies, one assessing HS with ultrasonography 10 and the other with computed tomography (CT) scans, 11 found prevalences of 31% and 37%, respectively. Although the main risk factors found in these studies were metabolic, another study compared two groups of patients with HS and different HIV status; the results showed that HIV-infected patients had lower body mass index (BMI) and lower body fat percentage.…”
mentioning
confidence: 99%
“…Guaraldi et al detected steatosis by CT scan in 37% of 225 HIV-monoinfected patients, and found an association with cumulative NRTI exposure (OR 1.12, 95%CI 1.03-1.22; P=<0.001) and obesity (OR 1.07, 95%CI 1.03-1.11; P<0.001) [23]. In contrast, in another study, though steatosis was present on US in 31% and by histology in 33% of 216 HIV-mono-infected patients, there was no association with either duration of HIV infection or ART, as only obesity (OR 2.1, 95%CI 1.6-2.8; P<0.001) and hypertriglyceridemia (OR 1.2, 95%CI 1-1.5; P=0.03) reached statistical significance [24]. Nevertheless, in both studies less than 30% of patients had deranged LFTs; this could possibly explain the lower prevalence of steatosis compared to our findings.…”
Section: Discussionmentioning
confidence: 66%
“…This is of great interest in view of the high prevalence of non-alcoholic fatty liver disease among HIV patients (currently estimated at 30-35% of monoinfected patients, i.e., those without concomitant hepatitis B or C infection). [38][39][40][41][42][43] Accelerated lipolysis in visceral adipose tissue undoubtedly contributes to the fatty liver phenotype, but we also found evidence pointing to additional mechanisms: diminished oxidative disposal of fatty acids and defective VLDL-triglyceride export. Evidence for the former was found in blunted expression of hepatic genes regulating fat oxidation (Ppara, Cpt1, Lcad, Aox), and for the latter in decreased expression of Mtp1, encoding microsomal triglyceride transfer protein which is critical for hepatic VLDL-TG export.…”
mentioning
confidence: 56%